Exploring nanoselenium to tackle mutated SARS-CoV-2 for efficient COVID-19 management - Singh, Avtar; Singh, Paramjit; Kumar, Rajeev; Kaushik, Ajeet (Frontiers in Nanotechnology, 2022)
Despite ongoing public health measures and increasing vaccination rates, deaths and disease severity caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and its new emergent variants continue to threaten the health of people around the world. Therefore, there is an urgent need to develop novel strategies for research, diagnosis, treatment, and government policies to combat the variant strains of SARS-CoV-2. Since the state-of-the-art COVID-19 pandemic, the role of selenium to deal with COVID-19 disease has been widely discussed due to its importance as an essential micronutrient. This review is aiming to provide all antiviral activities of nano-selenium (Nano-Se) ever explored using different methods in the literature. We systematically summarize the studied antiviral activities of Nano-Se required to project it as an efficient antiviral system as a function of shape, size, and synthesis method. The outcomes of this article not only introduce Nano-Se to the scientific community but also will motivate scholars to adopt Nano-Se to tackle any serious virus like mutated SARS-CoV-2 to achieve an effective antiviral activity in desired manner.